Report of the Committee on Unemployment Volume I - Planning Commission (Planning Commission, 1973)
The problem of unemployment and under-employment in the country has been causing serious concern to the Government in recent years. Great concern was expressed in Parliament and outside at the deteriorating situation in the country in respect of unemployment, particularly in the wake of the unprecedented severe droughts of 1965-66 and 1966-67, and of the subsequent serious industrial recession which afflicted the economy during two years (1966-63).
Government of India Ministry of Labour and Rehabilitation
Government of India Ministry of Labour and Rehabilitation